Interdigitated Back‐Contacted Carbon Nanotube–Silicon Solar Cells - Yuhua Bai; Qing Gao; Bingbing Chen; Wenheng Li; Xuning Zhang; Dehua Yang; Xueliang Yang; Jun Yan; Jingwei Chen; Jianming Wang; Dengyuan Song; Shufang Wang; et al. (Small Structures, 2023)
Carbon/silicon heterojunctions provide a new perspective for silicon solar cells and in particular those made from carbon nanotubes (CNTs) have already achieved industrial‐level power conversion efficiency and device size when using organic passivation and a back‐junction design. However, the current state of the art device geometry for silicon photovoltaics is the interdigitated back contact (IBC) cell and this has yet to be demonstrated for CNT/Si solar cells due to the complexity of fabricating the required patterns. Herein, IBC‐CNT solar cells are demonstrated via the simple spin coating of a conductive hole‐selective passivating film and the evaporation of buried silicon oxide/magnesium electron‐selective contacts for both polarities. The CNT coverage area fraction (fCNT) and the gap between the two polarities are optimized to minimize electrical shading loss and ensure high photocarrier collection. Large‐area (4.76 cm2) highly efficient (17.53%) IBC‐CNT solar cells with a Voc of 651 mV and Jsc of 40.56 mA cm−2 are demonstrated and are prepared with one alignment step for the CNT/Si contact, and photolithographic‐free and room‐temperature processes. These performance parameters are among the best for solution‐processed dopant‐free IBC schemes and indicate the feasibility of using low‐dimensional carbon materials in IBC solar cells.